Impact of Instagram Advertising on Youth Impulsive Buying Behavior Towards Apparel Outlets Located in Colombo District: The Moderating Effect of Consumer Personality and Mediating Effect of Digital Literacy - Wickramasinghe, M. M.; Wanninayake, W. M. C. B. (Department of Marketing Management, Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2021)
Social media advertisements are one of the most highly utilized communication tools in the current marketing landscape to engage with the audience. In Sri Lanka the most used social media platforms for advertising by companies are Facebook and Instagram. Both platforms can be used to influence on the impulsive purchase behavior of young consumes. The objective of this study is to evaluate the impact that social media advertisements, specifically Instagram advertisements, can have on the youth audience. The impulsiveness of making purchase decisions by youth has been studied in detail referring to the apparel outlets located in Colombo district of Sri Lanka with a moderating effect of consumer personality and mediating effect of digital literacy. The initial part of the paper reviewed previous literature for developing conceptual framework and hypotheses and then it was tested hypotheses based on qualitative findings developed from the questionnaire which was circulated among 384 young consumers who have been exposed to apparel related advertisements on Instagram. The practice gap and the theoretical gap has been identified to develop the conceptual framework where later the validity and reliability of the framework has been tested based on the data gathered using SPSS software. The hypotheses have been tested by using correlation and multiple regression analysis in deriving the conclusion where findings contribute to improving advertising content for better attraction and trial purchase of young consumers. In today’s context, social media advertising is of high importance and the impact of this on Sri Lankan apparel brand impulse purchases can be further investigated upon.
Keywords: Instagram Advertising, Para Social Interactions, Perceived Enjoyment, Perceived Usefulness, Social Media Advertisements